Is hip and lumbar-spine pain related to physiological characteristics in young elite gymnasts? - Steinberg, N.; Elbaz, L.; Bar-Sela, S.; Dar, G. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Gymnastics performances entail complex and extensive movements that require specific body morphology, strength, and flexibility that may lead to hip and lumbar-spine injuries. The present study aimed to evaluate the prevalence of hip and lumbar-spine pain and their associated physiological characteristics in young gymnasts.